HPB P18 The introduction of antimicrobial-coated sutures to reduce the rate of surgical site infections in the hepatopancreaticobiliary (HPB) department: a quality improvement project. (7th December 2022) - Lazzereschi, Lucia; Butcher, Lisa; Bond-Smith, Giles; Soonawalla, Zahir
Abstract: Background: Surgical site infections (SSIs) are the most common postoperative complication in developed countries. In the United Kingdom (UK), the most recent data from Public Health England showed that ten-year trends in SSI risk varied by surgical group, with the highest risk observed in hepatopancreaticobiliary (HPB) surgery. Several methods for SSI prevention have been researched and implemented in surgical practice such as appropriate antibiotic prophylaxis, hair removal and careful sterilisation of equipment. Due to their chemical composition, sutures utilised in abdominal surgery can promote bacterial colonisation. Antimicrobial-coated sutures have been manufactured to investigate if the addition of a synthetic, non-ionizing, broad-spectrum antimicrobial can prevents colonisation, reduce the rate of bacterial adherence and therefore decrease the rate of SSIs. In 2021, NICE released a statement advising the use of antimicrobial-coated sutures as part of a bundle of care in wound closure to prevent site infection after surgical procedures. Little research is available on the use of antimicrobial-coated sutures for anastomosis closure. We carried out a quality improvement project, assessing the rate of SSI with standard sutures, followed by the use of antimicrobial-coated sutures to investigate reduction on SSI rates for both anastomosis and skin closure. Methods: A quality improvement project, following the PDSA cycle, was carried out investigating rates of SSIs on all HPB patients undergoing an open procedure at Churchill Hospital, Oxford between November 2020 and June 2021. Data on SSI rates was collected electronically based on ward round entries, radiology and microbiology results. SSI were classified as 'superficial', 'deep' and 'organ' site infections based on the UK Health Security Agency (UKHSA) classification criteria. Antimicrobial-coated sutures were introduced in June 2021 and data was collected until November 2021. Chi-squared tests (X 2 ) were carried to compare SSI results between the two groups. Secondary analysis was carried out examining culture results for organ SSIs. Results: 167 patients had open operations between November 2020 and November 2021. 88 patients had standard sutures, 28/88 (32%) developed SSIs, of which 20/28 (71%) were organ SSIs. 79 patients had antimicrobial-coated sutures. 17/79 (22%) developed SSIs, of which 12/17 (72%) were organ SSIs. There was an overall 10% reduction in SSI rates [X 2 (1, N= 212) = 0.04, p-value > 0.05)]. Crucially, there was a reduction in positive cultures with antimicrobial-coated sutures, where 42% of samples sent for microbiology analysis, compared to 25% in standard sutures, were negative cultures [X 2 (1, N= 34) = 1.29, p-value > 0.05)]. Conclusions: There is reduction in superficial and organ SSIs when antimicrobial-coated sutures are utilised. Crucially, there is a marked reduction in positive cultures when these are used for anastomosis closure. As hepatopancreaticobiliary surgery has a high leak rate of 10–30% after resection, a proportion of patients will develop abdominal collections due to leaks and not due to infection. Further multi-centre studies with larger sample sizes need to be carried out within the HPB population to further investigate reduction in SSI caused by antimicrobial-coated sutures and the impact it has on microbiology cultures. Almost half of culture samples sent for microbiology analysis from radiologically confirmed organ SSIs grew negative cultures. Further research is needed to determine if the definition of what is considered an organ SSI in the HPB population needs changing and if the UKHSA criteria needs re-classification in this surgical group in light of both the percentage of negative cultures reported and the standard leak rate in these operations.